Konsep Kebebasan Manusia dan Hidayah dalam Perspektif Pendidikan Islam - Syakur Wildan; Sabarudin; Husni Idris; Awaliyah Karuniah Rahmah (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
The Humans as social beings have the authority and freedom to do what they want. Humans also try to provide creativity and innovation according to their abilities. It is hoped that this will benefit the local community. Humans are born as leaders to manage everything that is good and right on earth. The right to freedom in regulating must also be in accordance with the portion so that it does not deviate far from the ideals or goals. Besides that, guidance is one of the initial gates for humans to always be grateful and accept what God has given. This is because guidance is a guide for mankind which is expected to be accepted by humans sincerely and without coercion. The research method used was library research (literary study). The data sources were taken by the author from books, journals, scriptures, and other relevant references. Human freedom and guidance are an inseparable unit. Both are linked in daily actions day. Human freedom is inseparable from the guidance of Allah SWT. there are two things that are very important and useful, namely the value of humanism and the value of qonaah.